Alteration of B cell function by Epstein-Barr virus (Hematology Meeting Reports, 2009)
Epstein-Barr virus (EBV) is a DNA virus belonging to the g-herpes virus family. Over 90% of the human population worldwide is infected by the virus. Primary infection usually takes place during childhood and is mostly asymptomatic. However, when primary infection is delayed, frequently a self-limiting disease develops, called infectious mononucleosis (IM). During IM, a massive expansion of virus-harbouring cells is observed. These cells are then mostly eliminated by a strong cytotoxic T cell response. The cellular target of the virus and its reservoir during lifelong persistence are B lymphocytes, in which the viral genome is present as a circular episome. In healthy individuals, a stable balance is established between the expansion of virus-infected B cells and their elimination by cytotoxic T cells. However, EBV also plays a role in the pathogenesis of several human lymphomas. In vitro, EBV-infected B cells give rise to stable transformed cell lines, designated lymphoblastoid cell lines (LCL).